Higher Students' Anxiety Level and Factor in Writing Essays through Google Docs - Alfiandy Kamal (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
This study aimed to investigate the level and factors of anxiety experienced by higher students while writing essays through Google Docs. It used a quantitative data collection method collected through questionnaires adapted from the Second Language Writing Anxiety Inventory (SLWAI) by Cheng and ESL Writing Anxiety by Zhang using Five-Point Likert Scale. There were 10 participants in this study selected by using convenience sampling. The results showed an average anxiety score of 63, indicating moderate anxiety levels. The study identified that a lack of sufficient writing practice was students' primary cause of anxiety. Overall, this study provides valuable insights into the factors contributing to students' anxiety levels while writing essays through Google Docs. It can inform educators' strategies to support students in their writing assignments.